ANALYSIS OF EFFECTIVE USE OF FIXED ASSETS - S.N.Xadjibekov; I.B.Sapayev; R.O.Maxamadova; K.K.Naimova; M.B.Doniyorov; S.A.Farmonova; U.F.Ixmatova; Y.A.Komilov (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
The production program depends not only on the composition, structure, technical and condition of the main means, but also on their effective use. The summarizing indicator of effective use of fixed assets is the efficiency of fixed assets.